Idea et disegno : les projets de Cellini pour le sceau de l’Académie - Trottein, Gwendolyn (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2012)
The series of projects sketched and commented by the goldsmith-sculptor Benvenuto Cellini for the seal of the newly formed Accademia del disegno in Florence (1563) constitutes a curious milestone in the history of Idea in art. Artemis of Ephesus as the idea della natura, the nurturing goddess of disegno, figures on several of these drawings before giving way to her brother the sungod Apollo, described also as a god of nature and disegno, but of a disegno more rivalrous than foundational, and defined textually as of two types: idea in the artist’s mind or drawing with lines. But rather than succumbing to the growing tendency of the century to prize either of these aspects of disegno over the fully executed work of art, Cellini’s seals, despite the circumstances of their genesis and their esoterism, as several passages in the artist’s autobiography and technical treatises also attest, aim at affirming the overriding importance of art, especially figural sculpture, as tangible aesthetic object.